A Multinary Silver Cluster, Multicoordinated Silver Supramolecular Framework With a 2D Anionic Water Aggregation. Issue 10 (2nd October 2016) - Wang, Yuan-Yuan; Shi, Ruo-Bing; Pi, Min; Wang, Xiao-Fang; Jin, Chuan-Ming
Abstract : A new 3D supramolecular framework, [Ag6 (2-PyBIM)6 (ClO4 )6 (CH3 OH)2 (H2 O)11 ] (1 ) (2-PyBIM = bis[(2-pyridinyl)-imidazol-1-yl]methane), has been prepared and structurally characterized. Compound1 exhibits a 2D cationic network as a wave-like brick wall with a multi-coordinated Ag mode (di-, tri-, and tetranitrogen coordinated Ag centers) and multinary Ag cluster centers (Ag, Ag2, and Ag3 ) with the ligand-unsupported Ag—Ag interaction, encapsulated in an unprecedented 2D perchlorate-methanol-water layer of [(ClO4 )6 (CH3 OH)4 (H2 O)11 ] 6– anions. Additionally, the thermal stabilities and photoluminescence spectra of the complex1 are also discussed.